PENGARUH NET PROFIT MARGIN, DEBT TO EQUITY RATIO, EARNING PER SHARE, CURRENT RATIO TERHADAP HARGA SAHAM - Daniel Sardon Agustinus Marbun; Anissa Amalia Mulya (Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine the influence of Net Profit Margin, Debt to Equity Ratio, Earning Per Share, and Current Ratio on Stock Prices. In this research, Net Profit Margin, Debt to Equity Ratio, Earning Per Share, and Current Ratio are treated as the independent variables. Meanwhile, Stock Price acts as the dependent variable. This research utilizes secondary data from food and beverage subsector companies listed on the Indonesia Stock Exchange for the 2021–2024 period, with a sample of 51 companies. The sampling technique used is purposive sampling, and the analytical method is multiple linear regression. The results indicate that Debt to Equity Ratio has a negative influence on Stock Prices. Conversely, Net Profit Margin, Earning Per Share, and Current Ratio show a positive influence on Stock Prices